(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Control measures against electrical hazards in industrial facilities are given in the form of inspection checklists in standards and regulations. In these classic checklists, only the precautions against electric shock are checked within the scope of occupational health and safety. Industrial facilities have not only electrical shock hazards but also arc flash hazards. Therefore, checklists must include precautions against arc flash injuries. To design these measures, the magnitude of the arc flash incident energy must first be calculated. In this paper, the incident energy formula has been evaluated. In addition, new control lines have been added to the inspection checklist for precautions against arc flash hazards. Another important issue is the prioritization of the electrical installation checklist lines by calculating their importance weights. In this prioritization, the analytical hierarchy process, one of the multi-criteria decision-making techniques, was used. 23 experienced inspection engineers were interviewed to create a weighted prioritization table for the 33-line checklist. Thus, occupational safety professionals working in industrial facilities will be able to make an action plan for corrective actions using this prioritization table.